SINERGISITAS APBD DALAM MENCAPAI VISI MISI RIAU 2020 - Ikhwani Ratna (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
Riau Province is an area that has great natural potential. With this potential should live in the well-being of the people of Riau. To support the creation of a prosperous society and a prosperous then drafted vision and mission of Riau in 2020. To achieve the vision and mission in 2020, required an adequate local budgets. Synergy budget from year to year will be ushered right Riau realize the vision and mission of 2020. However, in practice, there are still many weaknesses in budgeting. Therefore, the budget needs to be prepared properly through Performance-Based Budgeting